2021
DOI: 10.1186/s12885-021-07855-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of survival in non-metastatic inflammatory and other T4 breast cancers: a SEER population-based analysis

Abstract: Background Previous studies have reported poor survival rates in inflammatory breast cancer (IBC) patients than non-inflammatory local advanced breast cancer (non-IBC) patients. However, until now, the survival rate of IBC and other T4 non-IBC (T4-non-IBC) patients remains unexplored. Methods Surveillance, Epidemiology, and End Results (SEER) database was searched to identify cases with confirmed non-metastatic IBC and T4-non-IBC who had received s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…With regard to the distribution of the molecular subtypes, 75% of the IBC tumors are classified in the more aggressive basal-like, HER2-positive and luminal B subtypes, as opposed to only 54% for non-IBC [ 3 ]. Patients with IBC generally have a worse survival than patients with non-IBC [ 2 ], potentially restricted to the triple-negative subtype [ 4 ]. Despite improvement of treatment regimens for breast cancer in time, patients with IBC are often excluded from trials investigating targeted therapies, and specific therapies for IBC are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the distribution of the molecular subtypes, 75% of the IBC tumors are classified in the more aggressive basal-like, HER2-positive and luminal B subtypes, as opposed to only 54% for non-IBC [ 3 ]. Patients with IBC generally have a worse survival than patients with non-IBC [ 2 ], potentially restricted to the triple-negative subtype [ 4 ]. Despite improvement of treatment regimens for breast cancer in time, patients with IBC are often excluded from trials investigating targeted therapies, and specific therapies for IBC are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The median age of diagnosis is generally lower for IBC in comparison with locally advanced non-IBC (57.3 years for IBC vs. 64.3 years for locally advanced non-IBC; refs. 13, 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…IBC is more likely to be estrogen receptor-negative and HER2-positive compared with non-IBC 8 , 9 . Besides, some researches have demonstrated that patients with IBC exhibited higher percentage of progesterone receptor-negative status compared with that of patients with non-IBC (55–56.7% versus 32–46.8%) 9 , 10 . While, it is still unknown whether the absence of PR expression will lead to worse prognosis of IBC or not.…”
Section: Introductionmentioning
confidence: 99%